Improved transduction of human corneal epithelial progenitor cells with cell-targeting adenoviral vectors - Chen, Zhuo (2006)
The development of vectors and techniques to transfer therapeutic genes to corneal epithelium has broad clinical applications. To determine if adenoviral (Ad5) vectors could be tailored to increase transduction of corneal epithelial progenitor cells expressing epidermal growth factor receptor (EGFR), the feasibility of targeting gene therapy vectors to genetically modify primary cultured human corneal epithelial cells (PHCEC) was evaluated. PHCECs were cultured from human limbal explants and transduced with Ad5 vectors containing the enhanced green fluorescent protein (GFP) reporter cassette to mediate gene transfer. The efficiencies of transduction with different Ad5 dosages and different time periods of exposure were compared. Metabolically biotinylated Ad5 vectors were retargeted to PHCECs using biotinylated epidermal growth factor (EGF) as a cell-targeting ligand. Phenotypes and function assays of transduced cells were determined by real-time PCR and BrdU incorporation. Ad5 vectors transduced approximately 50–93% of PHCEC at 10–100 PFU/cell in a dose-dependent manner and the transgene persisted for more than 2 weeks in vitro. Retargeting of biotinylated Ad5 with EGF increased transduction of EGFR and ABCG2-expressing corneal epithelial progenitor cells up to nine-fold and reduced transduction of K12 and involucrin-expressing differentiated corneal epithelial cells and had higher BrdU incorporation indexes. These data provide proof of principle that ligand-bearing modified Ad5 vectors can target a population of corneal epithelial progenitor cells for corneal gene therapy.